Contribution Of Arm Muscle Strength, Arm Muscle Explosive Power And Balance To The Bullets Reject Ability In Junior High School Students - M. Imran Hasanuddin; Hasyim Hasyim (JUARA : Jurnal Olahraga, 2023)
This study aims to determine; 1) is there a contribution between arm strength and the ability to shoot sideways style on SMP Negeri 19 Makassar students. 2). Is there a contribution between the explosive power of the arm muscles and the ability to shoot a sideways style shot at SMP Negeri 19 Makassar. 3). Is there a contribution between the balance and the ability to shoot sideways style on students of SMP Negeri 19 Makassar. 4) Is there a contribution between arm muscle strength, arm muscle explosive power and balance together on the sideways force shot put ability of SMP Negeri 19 Makassar students. The method used in this research is a quantitative descriptive method. The population in this study were all students at SMP Negeri 19 Makassar, totaling 115 students. The sample in this study amounted to 43 students. The sampling technique used simple random sampling (randomly). Based on the results of data analysis and hypothesis testing, it can be concluded as follows: 1) There is a significant contribution between arm muscle strength variables on the sideways force shot put ability of students of SMP Negeri 19 Makassar, amounting to 33.7% with an R value of 0.580 (Pvalue = 0.000 <Î± 0.05). 2) There is a significant contribution between the variable explosive power of the arm muscles to the ability to shoot sideways style bullets at SMP Negeri 19 Makassar, amounting to 65.2% with an R value of 0.807 (Pvalue = 0.000 <Î± 0.05). 3) There is a significant contribution between the balance variable on the sideways force shot-put ability of SMP Negeri 19 Makassar students, amounting to 22.2% with an R value of 0.471 (Pvalue = 0.001 <Î± 0.05). 4) There is a significant contribution between the variables of arm muscle strength, arm muscle explosive power and balance together on the sideways force shot put ability of students of SMP Negeri 19 Makassar, amounting to 75.5% with an R value of 0.869 (Pvalue = 0.000< Î± 0.05); and Fcount value of 40.124.